2014
DOI: 10.1111/lam.12211
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of rhamnolipids in microbial cell adhesion and biofilm development - an approach for control?

Abstract: Biofilms are omnipresent in clinical and industrial settings and most of the times cause detrimental side effects. Finding efficient strategies to control surface-growing communities of micro-organisms remains a significant challenge. Rhamnolipids are extracellular secondary metabolites with surface-active properties mainly produced by Pseudomonas aeruginosa. There is growing evidence for the implication of this biosurfactant in different stages of biofilm development of this bacterium. Furthermore, rhamnolipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(51 citation statements)
references
References 65 publications
2
49
0
Order By: Relevance
“…To date, whether rhamnolipids' multiple functions are caused by mere physical effects or are mediated by ligand– receptor‐mediated signaling events remain unclear . Our results here show that a mere physical mechanism is unlikely because the changes in surface properties, such as surface energy or surface tension, are unlikely to cause reversal and oscillation in the bioactivities.…”
Section: Resultsmentioning
confidence: 99%
“…To date, whether rhamnolipids' multiple functions are caused by mere physical effects or are mediated by ligand– receptor‐mediated signaling events remain unclear . Our results here show that a mere physical mechanism is unlikely because the changes in surface properties, such as surface energy or surface tension, are unlikely to cause reversal and oscillation in the bioactivities.…”
Section: Resultsmentioning
confidence: 99%
“…For enterobacteria, EAL proteins were found to be involved in regulating biofilm morphotype (El Mouali et al., ). The coordinated production of the microbial surfactant rhamnolipids using 2 quorum sensing systems, las and rhl , in P. aeruginosa has demonstrated that cell hydrophobicity can be increased by altering the properties of the microbial cell surface, increasing surface affinity and, consequently, initial adherence to the surface (Nickzad & Deziel, ). Furthermore, some of the components of the biofilm matrix, such as amyloid fibers, manifest affinity with the signaling molecules employed in the quorum sensin g system, retaining molecules which allows them to reach sufficiently high concentrations to be sensed by the different species that make up the biofilm (Flemming et al., ; Seviour et al., ).…”
Section: Quorum Sensingmentioning
confidence: 99%
“…The overall influence of BS29 and BS49 in their producer's growth indicates that they may have important implications in the progression of a culture made up of these micro-organisms. Albeit less explored than the biotechnological value of biosurfactants, it is known that these diverse compounds play critical roles in the survival of their producing micro-organisms by affecting biofilm architecture, facilitating nutrient transport, protecting bacterial biofilm from phagocytes or by acting as biocidal agents (Nickzad and Deziel 2014;Solano et al 2014). Biosurfactant are also known to increase cell permeability in bacteria (Sotirova et al 2008), which could explain their synergistic effects alongside some antibiotics (Joshi-Navare and Prabhune 2013).…”
Section: Resultsmentioning
confidence: 99%